Occurrence–regression–recurrence of hepatocellular carcinoma without any intervention: A case report - Li, Weinan; Xiong, Yongfu; Shu, Xia; Li, Jingdong (Frontiers in Surgery, 2022)
Background: Spontaneous regression of primary liver cancer is a rare event in nature. At present, the exact pathogenesis of spontaneous tumor regression is still unclear. Case Description: Clinical information was collected from a patient with spontaneous regression of liver cancer in our center. The patient was a 41-year-old male. He was admitted to the hospital due to aversion to fat or greasy food, anorexia, loss of appetite, and abdominal distension on May 3, 2019. Laboratory examination showed the following results: hepatitis B-associated markers: hepatitis B surface antigen (HBsAg) (+), hepatitis B e antigen (HBeAg) (+), and hepatitis B core antibody (HBcAb) (+); tumor markers: alpha-fetoprotein (AFP), 142,938.20 µg/L; abnormal prothrombin, 4,599.91 mAU/mL; and carbohydrate antigen 19-9 (CA19-9), 82.05 U/mL. Upper abdominal enhanced computed tomography (CT) indicated right hepatocellular carcinoma with portal vein tumor thrombus formation. The patient did not receive any treatment. The tumor in the right lobe of the liver completely regressed after 1 year, and the patient is still under follow-up. Conclusions: We reported a hepatocellular carcinoma patient undergoing a spontaneous regression process, but the exact pathogenesis remains unknown. Importantly, the pathogenesis of hepatocellular carcinoma spontaneous regression has the potentiality to become a treatment for hepatocellular carcinoma patients.